Gender Affects Skin Wound Healing in Plasminogen Deficient Mice - Rønø, Birgitte (Public Library of Science, 2013)
The fibrinolytic activity of plasmin plays a fundamental role in resolution of blood clots and clearance of extravascular deposited fibrin in damaged tissues. These vital functions of plasmin are exploited by malignant cells to accelerate tumor growth and facilitate metastases. Mice lacking functional plasmin thus display decreased tumor growth in a variety of cancer models. Interestingly, this role of plasmin has, in regard to skin cancer, been shown to be restricted to male mice. It remains to be clarified whether gender also affects other phenotypic characteristics of plasmin deficiency or if this gender effect is restricted to skin cancer. To investigate this, we tested the effect of gender on plasmin dependent immune cell migration, accumulation of hepatic fibrin depositions, skin composition, and skin wound healing. Gender did not affect immune cell migration or hepatic fibrin accumulation in neither wildtype nor plasmin deficient mice, and the existing differences in skin composition between males and females were unaffected by plasmin deficiency. In contrast, gender had a marked effect on the ability of plasmin deficient mice to heal skin wounds, which was seen as an accelerated wound closure in female versus male plasmin deficient mice. Further studies showed that this gender effect could not be reversed by ovariectomy, suggesting that female sex-hormones did not mediate the accelerated skin wound healing in plasmin deficient female mice. Histological examination of healed wounds revealed larger amounts of fibrotic scars in the provisional matrix of plasmin deficient male mice compared to female mice. These fibrotic scars correlated to an obstruction of cell infiltration of the granulation tissue, which is a prerequisite for wound healing. In conclusion, the presented data show that the gender dependent effect of plasmin deficiency is tissue specific and may be secondary to already established differences between genders, such as skin thickness and composition.